2015
DOI: 10.1021/nn505978r
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Thermal Annealing of CH3NH3PbI3for Highly Stable and Efficient Perovskite Solar Cells

Abstract: Solar cells incorporating lead halide-based perovskite absorbers can exhibit impressive power conversion efficiencies (PCEs), recently surpassing 15%. Despite rapid developments, achieving precise control over the morphologies of the perovskite films (minimizing pore formation) and enhanced stability and reproducibility of the devices remain challenging, both of which are necessary for further advancements. Here we demonstrate vacuum-assisted thermal annealing as an effective means for controlling the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
257
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(266 citation statements)
references
References 34 publications
(64 reference statements)
5
257
0
1
Order By: Relevance
“…[153,171] Xie et al reported vacuum-assisted thermal annealing methods using MAPbI3-xClx to avoid any vapor effect. [142] It is well-known that byproduct MACl gas is released during the formation of perovskite from MAI and PbCl2 precursors. [172][173][174] In this report, it is clearly demonstrated that the control of relative rates of MACl release and MACl generation is a key parameter for the production of high quality perovskite films without porosity.…”
Section: Vapor Induced Crystallizationmentioning
confidence: 99%
“…[153,171] Xie et al reported vacuum-assisted thermal annealing methods using MAPbI3-xClx to avoid any vapor effect. [142] It is well-known that byproduct MACl gas is released during the formation of perovskite from MAI and PbCl2 precursors. [172][173][174] In this report, it is clearly demonstrated that the control of relative rates of MACl release and MACl generation is a key parameter for the production of high quality perovskite films without porosity.…”
Section: Vapor Induced Crystallizationmentioning
confidence: 99%
“…This reduction is consistent with depletion of excess MAI by annealing. 25,37,39,43,46 However, the carbon content increased relative to nitrogen. Increasing carbon is consistent with transamidation.…”
Section: Discussionmentioning
confidence: 99%
“…Transamidation will consume one methylamine and replace it with one DMA, moving toward a 2:1 ratio of carbon to nitrogen. During annealing, MAI leaves the sample, 25,37,39,43,46 lowering the nitrogen, carbon, and iodine content in equal amounts. A combination of these two effects can be observed in Fig.…”
Section: Chemical Characterization By Xpsmentioning
confidence: 99%
“…According to Xie et al, the removal of CH 3 NH 3 Cl (MACl) improves greatly the device stability. 18 Since the mixing of CF helps to remove the DMF:DMSO mixture used for the precursor solution by reducing the solution viscosity, as exhibited by the predominant dependence of perovskite layer thickness on the rinsing spinning speed, it may also help to remove unreacted MACl dissolved in DMSO/DMF mixture. More studies are needed to investigate this possibility of chemical removal of MACl for improved reliability.…”
Section: -11mentioning
confidence: 99%
“…It is well known that thick perovskite layers with large grain sizes, complete surface overage and smooth surface morphology are required to produce high-efficiency PSCs. 11,[16][17][18] Improved planarity, which leads to higher uniformity in the active layer thickness, is also crucial for large-area PSCs because, like all other thin-film solar cells, large-area PSCs should be configured in cascaded structure of sub cells, which are limited in performance by the weakest link that deteriorates with increased non uniformity. Therefore, the simultaneous control over the crystallinity and the morphology of thick perovskite active layers is of paramount importance for the development of large-area PSCs.…”
Section: Introductionmentioning
confidence: 99%